67.7k views
2 votes
I need 6th question in the paper

I need 6th question in the paper-example-1
User ANIL MIRGE
by
5.5k points

2 Answers

1 vote
The correct and best answer is 8 using that formula
User Roman Cheplyaka
by
5.6k points
4 votes

Answer:

8

Explanation:


a = 1 - √(2)


(a - (1)/(a))^3 =


= ((a^2)/(a) - (1)/(a))^3


= ((a^2 - 1)/(a))^3


= (((a + 1)(a - 1))/(a))^3


= (((1 - √(2) + 1)(1 - √(2) - 1))/(a))^3


= (((2 - √(2))(-√(2)))/(1 - √(2)))^3


= (((-2√(2) + √(2)√(2))/(1 - √(2)))^3


= ((2 - 2√(2))/(1 - √(2)))^3


= ((2(1 - √(2)))/(1 - √(2)))^3


= 2^3


= 8

User Imclickingmaniac
by
6.1k points